KARAKTERISTIK PENDERITA SEPSIS NEONATORUM RAWAT INAP DI RSUD Dr. PIRNGADI MEDAN TAHUN 2010-2011 - Dewi Lestari; Sori Muda Sarumpaet; Hiswani . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2012)
Neonatal sepsis is a form of infectious disease in newborns with symptoms of systemic infection followed by bacteremia during the first month of life. Incidence of neonatal sepsis 1.5 to 3.72% in some referral hospitals in Indonesia with 37-80% CFR.To determine the characteristic of neonatal sepsis patients who are hospitalized at RSUD Dr. Pirngadi Medan in 2010-2011 with research descriptive case series design. Population and sample numbered 108 person (total sampling). Data obtained from medical records, analyze data using Chi-square, Mann Whitney dan ANOVA.The results obtained proportion of patients with neonatal sepsis based on the characteristics of infant is early neonatal 83.3%, sex ratio 1.8: 1, not twins 92.6% and low birth weight 56.5%. Proportion of patients with neonatal sepsis based on maternal characteristics such as age 20-35 years 74.1%, preterm gestational age 49.1%, 65.7% parity (2-4), 57.4% a history of normal birth, and Early-onset sepsis 82.4%, 36.1% instead of referral, 38,9% own expense, the average threatment time of 7 days, cured 63%. There was no difference in the proportion of neonatal sepsis classification based on the history of birth (p>0,05). There was no difference in the proportion of neonatal sepsis classification based on the origin of a referral (p>0,05), there was no differences in the average treatment time is based on the classification of neonatal sepsis (p>0,05), there are differences in the average treatment time is based on sources of cost (p<0,05) , there are differences in the average treatment time is based on the state of coming home (p< 0.05). To the Hospital Dr. Pirngadi Medan, in order to improve the quality of health care through curative efforts and particularly for the early diagnosis of neonatal sepsis reduces mortality and neonates, and to seek listing more complete patient data on the card status. Keywords: Neonatal Sepsis, Characteristics of Patients